(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the form of text, audio, videos and photographs, the Internet is a commonly used tool to exchange details. The long-distance exchange of information on a wide network needs encryption to secure the information from unauthorized access. The reliability of the network plays an important role in protecting data on an insecure network. Many encryption solutions have been discovered to protect the data on the network, and recent creative encryption schemes have been in demand since e-commerce e-banking and multimedia technologies are viewed on a regular basis on the internet. Cryptographic coding methods have lately been used primarily to protect unauthorized access to knowledge on an insecure network. The researchers also established many cryptographic strategies for protecting and efficiently transmitting knowledge on an insecure network. Image encryption techniques are commonly used by all cryptographic techniques to transmit photos on an insecure network. The purpose of this paper is to demonstrate the few encryption techniques that are used on an insecure network to encrypt the image. To encrypt the image, this paper proposes a new encryption technique. The suggested approach encrypts the image using Wavelet Transform, the Chaotic Mechanism, along with the production of the image fingerprint using the Hash function to be sent to the recipient. The suggested procedure, along with anonymity, often protects the image’s encryption.